Analisis Penyelesaian Kredit Macet (Studi pada Permodalan Nasional Syari’ah Cabang Kota Bengkulu) - Septina, Chindi; Yunus, Fatimah; Stiawan, Evan (GHAITSA : Islamic Education Journal, 2022)
The resaerch entitled “Analysis Of Settlement Of Bad Loans (Study On National Capital Madani Syari’ah Branch Of Bengkulu City )” has the intention of resolving bad loans through deliberations of all employees to find a solution to tha problems being faced, namely that all PNM Syari’ah employees are entitled to be responsible and authorized to bill the customer. In this study using a qualitative approach with descriptive methods. The data used are derived from primary and secondary data and the population in this study are employees from PT. Civil National Capital (Persero) Syari’ah Bengkulu city branch, totaling 13 people. The sampling technique by means of purposive sampling.